2019
DOI: 10.1186/s13046-019-1263-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC9 interacts with CPSF3 to regulate TGF-β signaling in colorectal cancer

Abstract: Background Colorectal cancer (CRC) is the third most frequent cancer and the second leading cause of cancer-related death worldwide. Increasing evidence indicates that the deregulation of long noncoding RNAs (lncRNAs) contributes to tumor initiation and progression; however, little is known about the biological role of cancer susceptibility candidate 9 (CASC9) in CRC. Methods Novel lncRNAs potentially involved in CRC tumorigenesis were identified from datasets downloade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 59 publications
(62 reference statements)
3
87
0
Order By: Relevance
“…[21][22][23] However, till now, there are only several lncRNAs have been mechanistically characterized in BC. LncRNA CASC9 has been demonstrated to serve as an oncogenic factor in plenty of human cancers, such as breast cancer, 24 colorectal cancer, 25 and lung adenocarcinoma. 26 A pan-cancer analysis revealed that CASC9 was strikingly overexpressed in bladder cancers, especially in urothelial carcinomas with squamous differentiation or pure squamous bladder cancers, indicating the potential role of CASC9 in BC.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] However, till now, there are only several lncRNAs have been mechanistically characterized in BC. LncRNA CASC9 has been demonstrated to serve as an oncogenic factor in plenty of human cancers, such as breast cancer, 24 colorectal cancer, 25 and lung adenocarcinoma. 26 A pan-cancer analysis revealed that CASC9 was strikingly overexpressed in bladder cancers, especially in urothelial carcinomas with squamous differentiation or pure squamous bladder cancers, indicating the potential role of CASC9 in BC.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs dominate the upstream portion of the RNA network and function as primary effectors of mRNAs, and several lncRNAs are identi ed as potential prognostic factors in COAD [20,30]. Among these 14 lncRNAs in the model, PCAT6, CASC9, MIR4435-2HG, SNHG16, and LINC00513 have been reported to play a role in the pathogenesis and prognosis of various cancer types (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). For example, CASC9 has been reported to be upregulated and conferred an oncogenic function in human hepatocellular carcinoma, oral carcinoma, gastric cancer, colorectal cancer, and esophageal cancer [28,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, CASC9 was found to be negatively correlated with the miR-193a-5p expression, and promoted tumorigenesis via the miR-193a-5p/ERBB2 axis [34]. Luo et al [35] reported that the higher expression of the oncogenic CASC9 was associated with poor patient outcomes when interacting with CPSF3 to regulate TGF-β signaling. Consistently, it has been reported that the higher expression of PCAT6 was correlated with poorer clinical outcomes and further found that PCAT6 was able to inhibit cell apoptosis by regulating the anti-apoptotic protein ARC expression via the EZH2 in COAD [36].…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, the cancer susceptibility candidate 9 ( CASC9 ) is a lncRNA that predicts poor survival for patients 37 . The pro‐tumorigenic function of CASC9 is due to the increased stabilization of TGFB2 levels, which lead to active TGF‐β2 signaling and enhanced p‐Smad3 levels 37 . The positive contribution of CASC9 to TGF‐β signaling depends on its binding to the protein cleavage and polyadenylation specific factor 3 (CPSF3), an mRNA‐processing factor, which is capable of directly interacting with TGFB2 mRNA 37 .…”
Section: Lncrnas Act As Regulators Of Tgf‐β Signalingmentioning
confidence: 99%